The PPARα/γ Agonist, Tesaglitazar, Improves Insulin Mediated Switching of Tissue Glucose and Free Fatty Acid Utilization In Vivo in the Obese Zucker Rat - Kristina Wallenius; Ann Kjellstedt; Pia Thalén; Lars Löfgren; Nicholas D. Oakes (PPAR Research)
Metabolic flexibility was assessed in male Zucker rats: lean controls, obese controls, and obese rats treated with the dual peroxisome proliferator activated receptor (PPAR) agonist, tesaglitazar, 3 μmol/kg/day for 3 weeks. Whole body glucose disposal rate () and hepatic glucose output (HGO) were assessed under basal fasting and hyperinsulinemic isoglycemic clamp conditions using [3,3H]glucose. Indices of tissue specific glucose utilization () were measured at basal, physiological, and supraphysiological levels of insulinemia using 2-deoxy-D-[2,6-3H]glucose. Finally, whole body and tissue specific FFA and glucose utilization and metabolic fate were evaluated under basal and hyperinsulinemic conditions using a combination of [U-13C]glucose, 2-deoxy-D-[U-14C]glucose, [U-14C]palmitate, and [9,10-3H]-(R)-bromopalmitate. Tesaglitazar improved whole body insulin action by greater suppression of HGO and stimulation of compared to obese controls. This involved increased insulin stimulation of in fat and skeletal muscle as well as increased glycogen synthesis. Tesaglitazar dramatically improved insulin mediated suppression of plasma FFA level, whole body turnover (), and muscle, liver, and fat utilization. At basal insulin levels, tesaglitazar failed to lower HGO or compared to obese controls. In conclusion, the results demonstrate that tesaglitazar has a remarkable ability to improve insulin mediated control of glucose and FFA fluxes in obese Zucker rats.